A UNDERSTANDING OF HADITH BASED ON SOCIOLOGICAL APPROACH: (Reinterpretation of Mahram for Women's Travel Accompaniment) - Ulum, Bachrul; Fatmawati, Fatmawati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Grasping hadith in any methodology, including the humanistic angle, will empower new translations that adjust to the circumstances and circumstances of the times. This becomes critical when strict issues can't be settled absolutely literarily. Taking care of issues in a specific period expects that there be an adjustment of understanding of hadith texts in light of existing real factors. So the unbending nature of importance won't happen, and on second thought the normal adaptability, without setting to the side the current standards. With the goal that the significance of mahram in examining this hadith requires an adjustment of the importance contained in that. The job of ladies at the hour of the Prophet was not equivalent to that of ladies in the current period. The contribution of ladies in friendly, social and financial perspectives expects ladies to have a major offer in propelling world progress. Not just around the kitchen region, beddings and wells. So the significance of mahram isn't simply private yet coordinated to the security framework that is felt by ladies in their wellbeing